2023
DOI: 10.1007/s00262-023-03425-3
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibition combined with targeted therapy using a novel virus-like drug conjugate induces complete responses in a murine model of local and distant tumors

Abstract: Metastases remain the leading cause of cancer-related death worldwide. Therefore, improving the treatment efficacy against such tumors is essential to enhance patient survival. AU-011 (belzupacap sarotalocan) is a new virus-like drug conjugate which is currently in clinical development for the treatment of small choroidal melanoma and high-risk indeterminate lesions in the eye. Upon light activation, AU-011 induces rapid necrotic cell death which is pro-inflammatory and pro-immunogenic, resulting in an anti-tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The International Classification of Diseases (ICD) and favorable microenvironment triggered by Bel-sar treatment are indicators for combination with immune check point inhibitors to induce the local and distant tumor cure. 16 , 17 , 63 Further preclinical and clinical studies to investigate the combination Bel-sar treatment and immune checkpoint inhibitors should be conducted. Our results indicate that despite the light-absorbing function of pigments, which was proposed to be detrimental for laser therapy, we could show that Bel-sar treatment can enhance antitumor immune effects even in pigmented malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The International Classification of Diseases (ICD) and favorable microenvironment triggered by Bel-sar treatment are indicators for combination with immune check point inhibitors to induce the local and distant tumor cure. 16 , 17 , 63 Further preclinical and clinical studies to investigate the combination Bel-sar treatment and immune checkpoint inhibitors should be conducted. Our results indicate that despite the light-absorbing function of pigments, which was proposed to be detrimental for laser therapy, we could show that Bel-sar treatment can enhance antitumor immune effects even in pigmented malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…We recently published a paper stating that combining either PDT or light-activated Belzupacap sarotalocan (Bel-sar) with an immune checkpoint inhibitor induces a better antitumor response in mice than either treatment alone. 16 , 17 …”
mentioning
confidence: 99%
“…Kim et al suggested that the combination of the rho-kinase (ROCK) inhibitor ripasudil, PD0L1 inhibitor, and local photodynamic therapy (PDT) could reduce the primary tumor burden and prevent metastasis in an orthotopic intraocular melanoma model [ 56 ]. A new virus-like drug conjugate (AU-011) and the inhibitor of the receptor for the hepatocyte growth factor (HGF) are also worth studying in systemic treatment combined with ICIs [ 57 , 58 ].…”
Section: Current Status Of Clinical Studies Regarding Icis In Patient...mentioning
confidence: 99%
“…With a similar conclusion, Kashyap et al also found a potential association between higher LAG3 expression and shorter metastasis-free survival [ 74 ]. An in vivo experiment by Huis In 't Veld et al showed a CR rate of 75% in a murine model with distant MC38 tumors after treatment with AU-011 and a LAG3 inhibitor [ 57 ]. Thus, by observing valuable results from in vitro and in vivo experiments, the clinical effect of antibodies against LAG3 in UM, especially in the process of tumor metastasis, deserves to be investigated and validated.…”
Section: Current Status Of Clinical Studies Regarding Icis In Patient...mentioning
confidence: 99%
“… 9 , 30 We recently showed that treatment with AU-011 and ICIs induced an abscopal effect in a murine model using MC38 cells. 28 Prior in vitro tests showed that AU-011 worked well on UM cell lines.…”
mentioning
confidence: 99%